National identity in an emerging information society: some problematic issues - Kostytsky, Mychailo V.; Kushakova-Kostytska, Nataliia V.; Gvozdik, Oleg I.; Kravets, Vitalii M.; Shkarupa, Kostiantyn V. (Cuestiones Políticas, 2020)
The objective of the article is to characterize the national identity in an emerging information society. The multidimensionality, internal contradictions, and variability of the phenomenon of national identity led to methodological pluralism, the application of various methods and principles. Thus, during the research, historical and philosophical, dialectical, phenomenological, and systemic approaches, structural and functional methods were used. The article considers the problems related to the development of the information society and the preservation of national identity, including the peculiarities of this process in modern Ukrainian society. The development factors of the information society that influence national and individual consciousness and promote their optimal interaction are defined. In addition, some possible trends in a further globalization of modern society are analyzed, its cultural, economic, national, and political unification, as well as its consequences for Ukraine. By way of conclusion, it is stated that the positive example of several countries gives hope for a favorable relationship between the development of the information society and the preservation of national cultures through the strengthening of national identity and the reactivation of spiritual values.